Clinical Results of Nonvascularized Metatarsal Articular Bone Grafting for Osteochondral Defects of the Radiocarpal and Distal Radioulnar Joint - Stougie, Shirley D.; Hoogvliet, Peter; Plugge, Lara; Coert, J. Henk (Journal of Wrist Surgery, 2023)
Background Treatment of post-traumatic osteochondral defects in the radiocarpal and distal radioulnar joint with nonvascularized metatarsal articular bone grafting is an option to restore the joint (cartilage) surface and wrist function.Purpose To evaluate the clinical midterm results of 10 consecutive patients who were treated with a nonvascularized metatarsal bone graft for cartilage bone defects of the lunate facet, scaphoid facet, sigmoid notch, or the radial part of the ulnar head.Patients and Methods Patients with isolated osteochondral defects of the lunate facet, scaphoid facet, sigmoid notch, or radial part of the ulnar head, respectively, as a result of wrist trauma were retrospectively identified in a prospectively collected database. The patients symptoms were limited wrist motion and/or pain. Clinical results and complications were extracted from patient's medical files and two questionnaires consisting of the Patient-Rated Wrist Evaluation and additional questions regarding patient satisfaction and return to work and/or hobby.Results Minor complications occurred in three cases and required surgery. In five cases an acceptable donor site foot morbidity was seen at 1 year. One patient was not satisfied due to persistent wrist pain despite adequate range of motion. One patient could not return to its prior work. Another patient could not resume its hobby.Conclusion Retrospective evaluation of 10 cases with resurfacing of the scaphoid facet, sigmoid notch, and/or lunate facet, or radial part of the ulnar head has shown that osseointegration was possible without a vascular pedicle to the graft in all cases with a (mean) follow-up of 5 years. This technique may become an alternative treatment when implants become less available.Level of Evidence Level III
Keywords: nonvascularized; bone graft; metatarsal